Visual evoked potential repeatability using the Diopsys NOVA LX fixed protocol in normal older adults - Trevino RC (Dove Medical Press, 2018)
Richard C Trevino,1 Carolyn E Majcher,1 Adreain M Henry,1 Melinda Rodriguez,1 William E Sponsel1–3 1Rosenberg School of Optometry, University of the Incarnate Word, San Antonio, TX, USA; 2WESMDPA Baptist Medical Center Glaucoma Service, San Antonio, TX, USA; 3Department of Biomedical Engineering, University of Texas San Antonio, San Antonio, TX, USA Purpose: The purpose of this study was to evaluate the intrasession and intersession repeatability of visual evoked potentials in normal adults over 40 years of age as recorded using the Diopsys NOVA LX fixed protocol.Methods: Inclusion criteria were adults aged over 40 years with best corrected distance acuity of 20/40 or better in each eye. Subjects underwent three consecutive visual evoked potential examinations using the Diopsys NOVA LX fixed protocol. All examination procedures were carried out in accordance with the manufacturer recommendations. To assess intersession repeatability, nine subjects returned in 2–6 weeks for repeat examination.Results: A total of 46 subjects were recruited. Mean ± SD age: 53±9 years (range: 40–84 years); 69% of subjects were female and 80% were non-white. Coefficients of variation (CVs) and intraclass correlation coefficients (ICCs) revealed greater repeatability for P100 latency (CV: 3%–7%; ICC: 0.39–0.76) than for P100 amplitude (CV: 21%–33%; ICC: 0.34–0.69) and greater repeatability for recordings made with high contrast stimuli (amplitude CV: 21%–23%; latency CV: 3%–7%) than low contrast stimuli (amplitude CV: 24%–33%; latency CV: 6%–7%). Minimum detectable change values ranged between 4.50 and 9.95 µv for amplitude and 8.16–15.26 ms for latency. Repeatability was not influenced by age, sex, or race.Conclusion: The Diopsys NOVA LX fixed protocol demonstrated clinically acceptable intrasession and intersession repeatability in these healthy older adults, with latency being more repeatable than amplitude and examinations employing high contrast stimuli being more repeatable than those using low contrast stimuli. Keywords: electrophysiology, visual evoked potential, glaucoma, repeatability